Ransomware: Evolution, Target and Safety Measures - Maurya, AK; Kumar, N; Agrawal, A; Khan, RA (International Journal of Computer Sciences and Engineering, 2025)
Security was a big deal for a long time. With the viruses, malware and ransomware are another problems seen by the practitioner. This paper shows working of ransomware with its evolution and general characteristics of few popular ransomware. In evolution part, the paper provides s study from first ransomware to current days. The study shows the light on various kind of infection performed by a ransomware including data infection and infected machine. Different attackers made choices to the target various attack; the paper provides a sight on various target types of the ransomware. This paper trying to demonstrate few ransomware attacks case studies to show the problem created by various ransomware as an example. After an attack, what a victim should do after infection is also discussed at the end of the paper. How people can save their system and what are the safety measures to save the system from ransomware, are also discussed by the researcher. At the end of the paper, the researcher points out few steps to save systems and data.